The balance of intrapersonal, interpersonal, and extra-personal values and its relationship to life satisfaction and resilience in Japan and the United States - Aiko Murata; Miki Yokoyama; Miki Yokoyama; Wataru Akahori; Junji Watanabe; Junji Watanabe (Frontiers in Psychology)
Previous studies have shown that the values essential to well-being vary across individuals and cultures. Most cross-cultural well-being studies have focused on cultural differences related to the importance of specific values such as achievement and universalism. Recently, however, some researchers focusing on East Asian cultures have noted the importance of wholeness, integration, and balance in well-being, where individual, social, and environmental factors are harmoniously integrated. The current study focuses on the balance individuals strike among each of the following values: (1) intrapersonal values, which they fulfill personally; (2) interpersonal values, which they fulfill in their relationships with others; and (3) extra-personal values, which they fulfill in their relationships with society as a whole and the greater world. Specifically, two aspects of the balance of values: (A) Value Diversity: the extent of diversity in value selection by identifying how many of the three predefined value categories were chosen, (B) Value Proportion: the relative emphasis placed on each value category by identifying which of the three value categories was selected more frequently. Using a large-scale online survey, we explored the relationship between the balance of values and life satisfaction (satisfaction with one’s current life) and resilience (the tendency to recover from negative events) among participants in Japan (n = 5,219) and the United States (n = 4,818), spanning various age and socioeconomic groups. The results indicated that, regardless of country, individuals with greater Value Diversity exhibited higher resilience. Those who placed greater emphasis on extra-personal values also tended to be more resilient. In Japan, but not in the United States, a stronger emphasis on extra-personal values was associated with higher life satisfaction. These findings suggest that while the relationship between Value Proportion and life satisfaction differs across cultures—being observed in Japan but not in the United States—the balance of multiple values, rather than reliance on a single value type, appears to contribute to the resilience that supports future well-being in both countries, and thus not only in East Asian cultures.